CONTENT ANALYSIS OF STORYTELLING ELEMENTS AND BRAND ARCHETYPE OF LINKEDIN AD CAMPAIGN - Maatota, Fyolin T.; Lapian, Joyce S.L.H.V.; Tielung, Maria V.J. (Universitas Sam Ratulangi, 2019)
Abstract: In a brand management context, storytelling became a valuable instrument to positively affect consumer brand perception and related behavior. With LinkedIn as the object, this research purpose is to understand how it integrates its ad campaign and develops its storytelling. This research is a qualitative exploratory research and content analysis is used to analyze the data. The result shows that LinkedIn use storytelling to communicate messages that reflect on the company core values. Through the campaign, LinkedIn present peopleâ€™s life experiences and conflict that their members who is trying to establish career and passion can relate to. The dominant subthemes: Opportunity, Passion and Caring shows how the conflict rising when the ad representative trying to do or keep doing what they believe and passionate about. This story also progress in: The Quest, Rags to Riches, and Overcoming the Monster storylines. Additionally, LinkedIn is depicted with the archetype of Caregiver as a connector that helps its member to achieve their mission and goals. For brands and marketer, it is recommended to make ads more relatable with everyday lives, including the consumer to participate and build a communication and relationship through more living experience and dialogues.Â Keywords: storytelling, brand archetypes